The “Paulo Fraire” Educational Thinking Paradigm in the Service Learning Model in Higher Education - Ardhana Januar Mahardhani; Prihma Sinta Utami (STAI Hubbulwathan Duri, 2022)
he study of writing this article is focused on discussing the concept of an educational paradigm of thinking about problems or problem-posing offered by Paulo Fraire's character in relation to the implementation of lecture activities combined with the service-learning model. The purpose of writing this article will be focused on seeing how the implementation pattern or learning stage model uses the problem-posing paradigm of Paulo Freire's thinking which will be linked to the service-learning model. The method in writing this article uses the literature review method. The literature review was carried out by analyzing journals in the 2010-2021 period related to the study of Paulo Fraire's paradigm of thinking about problem posing and theoretical studies on the implementation of service-learning. From the results of the analysis of related journals found 15 journals that can be used as a reference for the analysis. Based on the findings of the integration of the service-learning model and problem posing, it was found that 4 steps can be taken, namely: listening, action, reflection, and demonstration. Paulo Fraire's paradigm of thinking about education facing problems or problem posing is based on the phenomenon of education with the